PERSONAL NOISE EXPOSURE ON MINING WORKERS - Kepeski, Andrej; Mirakovski, Dejan; Hadzi-Nikolova, Marija; Doneva, Nikolinka (Natural Resources and Technology, 2016)
Occupational exposure to high noise levels represents a problem almost inall service providing and goods producing industries, but according to availabledata, this problem is most pronounced at workers in transportation, mining andconstruction. Excessive exposure to high noise levels poses a serious dangerto the miners` health which can lead to poor verbal communication and reducetheir ability to recognize warning signals. Miners in surface and undergroundmines are exposed to high noise levels, resulting primarily from heavy andnoisy machinery, while in underground mines the limited and closed spacefurther increases the problem of exposure to high noise levels.This paper presents the results of measured noise level at main sources inmining as well as personal noise exposure of miners.